2015
DOI: 10.1007/s11906-015-0590-9
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Blood Pressure Monitoring in the Diagnosis, Prognosis, and Management of Resistant Hypertension: Still a Matter of our Resistance?

Abstract: Resistant hypertension, commonly described as the failure to achieve goal blood pressure (BP) despite an appropriate regimen of three antihypertensive drugs at the maximal tolerated doses, one of which is diuretic, is increasingly recognized as an important problem of public health. Large population studies with office measurements suggest that the prevalence of resistance hypertension is approximately at 6-12 % of the general hypertensive population and 8-28 % of treated hypertensives. However, these estimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
10

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 54 publications
(40 reference statements)
0
20
0
10
Order By: Relevance
“…A HAR verdadeira, diagnosticada pelo MAPA, tem o dobro do risco CV em comparação à HAR relacionada a efeito do avental branco. 18 De modo geral, as médias de PA obtidas nos três períodos do MAPA são fortes preditoras de risco CV, enquanto a PA de consultório não demonstrou nenhum valor prognóstico. 18 , 19 Estudos longitudinais destacaram a PA no sono elevada e a ausência de descenso noturno como importantes preditores de risco CV.…”
Section: Aspectos Prognósticosunclassified
“…A HAR verdadeira, diagnosticada pelo MAPA, tem o dobro do risco CV em comparação à HAR relacionada a efeito do avental branco. 18 De modo geral, as médias de PA obtidas nos três períodos do MAPA são fortes preditoras de risco CV, enquanto a PA de consultório não demonstrou nenhum valor prognóstico. 18 , 19 Estudos longitudinais destacaram a PA no sono elevada e a ausência de descenso noturno como importantes preditores de risco CV.…”
Section: Aspectos Prognósticosunclassified
“…Therefore, ambulatory BP monitoring (ABPM) might be more accurate than clinical BP measurement; it allows the detection of nocturnal BP and dipping patterns, and can reduce false-positive results by detecting white-coat hypertension, and false-negative results by detecting masked hypertension [5]. Indeed, several studies have shown the superiority of ABPM over office-or home-based BP monitoring to detect hypertension and predict cardiovascular outcomes [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Up to 28% of treated hypertensive patients have resistant hypertension, defined as requiring a minimum of three antihypertensive medications including a diuretic in order to achieve normotension (59). Out-of-office blood pressure monitoring can be particularly useful in the verification and management of treatment-resistant hypertension.…”
Section: Drug-resistant Hypertensionmentioning
confidence: 99%
“…Additionally, poor adherence is a common issue, and may result in misperceived resistance to medication, known as pseudoresistance (59,61). As a result, patients may be prescribed a greater number of medications, at higher doses than indicated, increasing the risk of hypotension and other adverse effects when they do take their medications.…”
Section: Drug-resistant Hypertensionmentioning
confidence: 99%